Urban open spaces for adolescent girls: An assessment for Islamabad and Rawalpindi, Pakistan - Qutub, Syed Ayub; Anjum, Nomana (International Food Policy Research Institute, 2015)
Urban open spaces are valued for their health, social, economic, and environmental benefits. Outdoor physical activity is important for the wellbeing of youth, while playfulness is crucial for creativity and innovation. It is observed that in Pakistan the access of adolescent girls to public open spaces and school playgrounds is restricted, but there has been no prior scientific study. This research has studied the impediments in four planned and un-planned localities of Islamabad and Rawalpindi. The restrictions on girls are pervasive and become more severe upon their attaining puberty. The values of city and local parks as adolescent-girl-friendly spaces (AGFS) have been assessed. The project has developed AGFS designs for parks and playgrounds, and tested the preferences of the target beneficiaries. Adolescent girls prefer creative play spaces with loose materials and cycling over fixed play fixtures. Institutional and programmatic interventions are proposed on the basis of the findings and consultations.